2004
DOI: 10.4049/jimmunol.172.3.1661
|View full text |Cite
|
Sign up to set email alerts
|

The Nonclassical MHC Class I Molecule Qa-1 Forms Unstable Peptide Complexes

Abstract: The MHC class Ib molecule Qa-1 is the primary ligand for mouse CD94/NKG2A inhibitory receptors expressed on NK cells, in addition to presenting Ags to a subpopulation of T cells. CD94/NKG2A receptors specifically recognize Qa-1 bound to the MHC class Ia leader sequence-derived peptide Qdm. Qdm is the dominant peptide loaded onto Qa-1 under physiological conditions and this peptide has an optimal sequence for binding to Qa-1. Peptide dissociation experiments demonstrated that Qdm dissociates from soluble or cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 39 publications
4
35
0
Order By: Relevance
“…Previous studies have shown that class I expression on DC protects from NK cell-mediated lysis in vitro [18, 20, [26]. This finding was further tested and confirmed in this study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Previous studies have shown that class I expression on DC protects from NK cell-mediated lysis in vitro [18, 20, [26]. This finding was further tested and confirmed in this study.…”
Section: Discussionsupporting
confidence: 87%
“…DC were checked for viability prior to use. For the stabilization of Qa1 b on the surface of the DC, DC were incubated overnight in the presence of the Qdm peptide (AMAPRTLLL) or its control peptide Qdm-4C (AMACRTLLL) as previously described [26].…”
Section: Methodsmentioning
confidence: 99%
“…However, it has recently been shown that Qa-1 and HLA-E are unstable at the cell surface in comparison to classical MHC class I. These nonclassical class Ib molecules thus require a continuous supply of cognate peptide to maintain cell surface expression and thence mediate effective NK cell inhibition (45). One possibility to explain the specificity of MHC class I down-regulation is that vaccinia virus inhibits host protein synthesis (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…The non-classical major histocompatability class I proteins serve as ligands for receptors on natural killer cells and g/d T cells. 29,30 It is clear from this small set of genes that the IRF-3 transcription factor acts to elicit widespread immune responses.…”
Section: Irf-3-dependent Direct Response Genesmentioning
confidence: 99%